Optimizing Bacterial Cellulose Production From Kombucha Tea Utilizing Molasses and Tea Dust in Growth Medium - Suriyapriya Selvaraj; Kalaichelvan Gurumurthy (International Journal of Polymer Science)
Kombucha, a potentially probiotic beverage renowned for its health benefits, was brewed using sweetened tea and a microbial consortium known as symbiotic culture of bacteria and yeast (SCOBY). This study is aimed at optimizing SCOBY production media using economical substrates through the Taguchi method of response surface methodology (RSM). Kombucha production was optimized for SCOBY yield by utilizing tea dust as a nitrogen source instead of tea leaves and blackstrap molasses as a carbon source. The cost per liter of the optimized medium was reduced to $0.027 (optimized) from $0.075 (unoptimized). The SCOBY yield was higher in the optimized condition (2.56%) compared to the control (2.44%) by Day 10. Optimal conditions for maximal SCOBY yield (2.56%) included 75 g/L molasses, 10 g/L tea dust, 20 g/L SCOBY seeding, pH 5, and an incubation temperature of 30°C. The growth rate (μ) of SCOBY was marginally higher in the test sample (1.142 kg/day) compared to the control (1.136 kg/day). The cost difference in SCOBY production between control and test samples was 97.8%, considering current raw material prices. Utilizing cost-effective substrates, bacterial cellulose from kombucha fermentation could be feasibly commercialized within a short timeframe.